2001
DOI: 10.1292/jvms.63.17
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Stromal-Vascular Cells Isolated from Canine Adipose Tissues in Primary Culture.

Abstract: ABSTRACT. A culture condition supporting adipocyte differentiation of stromal-vascular (S-V) cells isolated from canine adipose tissues was established. Morphological observation and determination of glycerol-3-phosphate dehydrogenase (GPDH) activity were used as the criteria for adipocyte differentiation. After reaching confluence, the cells were able to undergo terminal adipocyte differentiation by treatment with 100 µM indomethacin, 10 µg/ml insulin and 0.5 mM 1-methyl-3-isobutylxanthine (MIX) in medium sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 39 publications
(39 reference statements)
0
23
0
Order By: Relevance
“…In a recent study using SVCs isolated from a variety of canine adipose tissue, the rate of differentiation to mature adipocytes was significantly lower from omental SVCs than from perirenal, subcutaneous or inguinal SVCs under the same medial conditions (Wu et al, 2001). Although peroxisome proliferator-activated receptor (PPAR)-g agonists are known to promote differentiation (Shao and Lazar, 1997;Wu et al, 1999) and maturation in adipocytes (Okuno et al, 1998), they increase the weight of only subcutaneous white and brown adipose tissues but not visceral white adipose tissue in rats in vivo (Berthiaume et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…In a recent study using SVCs isolated from a variety of canine adipose tissue, the rate of differentiation to mature adipocytes was significantly lower from omental SVCs than from perirenal, subcutaneous or inguinal SVCs under the same medial conditions (Wu et al, 2001). Although peroxisome proliferator-activated receptor (PPAR)-g agonists are known to promote differentiation (Shao and Lazar, 1997;Wu et al, 1999) and maturation in adipocytes (Okuno et al, 1998), they increase the weight of only subcutaneous white and brown adipose tissues but not visceral white adipose tissue in rats in vivo (Berthiaume et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…This was followed by two washes before resuspension in erythrocyte lysis buffer for maximally 10 min. Finally, cells were resuspended in inoculation medium [52], counted with a haemocytometer and diluted in inoculation medium to a plating density of 40,000-60,000 cells/cm 2 . The cells were cultured at 37°C in a humidified atmosphere of 5% CO 2 /95% air.…”
Section: Cell Culturementioning
confidence: 99%
“…The cells were cultured at 37°C in a humidified atmosphere of 5% CO 2 /95% air. After 72 h, the preconfluent cells were washed three times with PBS and the inoculation medium replaced by induction medium; after 48 h, the induction medium was replaced by feeding medium which was renewed every 48 h [52]. All culture media contained 100 U/ml penicillin, 100 µg/ml streptomycin and 2.5 µg/ml amphotericin B (Invitrogen).…”
Section: Cell Culturementioning
confidence: 99%
“…Adipose tissue-derived stromal Cells (ATSCs): ATSCs were prepared according to the method of Wu et al [22]. Briefly, celiac adipose tissues were collected aseptically from 1-to 2-years-old beagle dogs under general anesthesia [4].…”
Section: Methodsmentioning
confidence: 99%
“…Among various adult stem cells, adipose tissue-derived stromal cells (ATSCs) are multipotential adult mesenchymal stem cells and differentiate into mesenchymal lineage cells such as adipocytes, osteocytes, chondrocytes, and myocytes [22,24]. Recently, Ashjian et al [1] reported that ATSCs was able to differentiate into nonmesodermal cells included ectodermal neural cells.…”
mentioning
confidence: 99%